Multiaxial Fatigue Behaviour Of Heat Treated 6061 Aluminium Alloy - Marno, Marini (2011)
This study is devoted to investigate the response of solid and thin-walled tubular specimen made of as-received and heat treated into T4 and T6 6061 aluminium alloy subjected to axial (tension-tension), torsional and axial torsional low cycle fatigue. 6061 aluminium alloys have been widely used as a candidate material in aerospace, automobile, aircraft and structural application because of their superior mechanical properties such as high strength to weight ratio and good ductility. In this investigation, the response and behaviour of this alloy to the cyclic loading were studied using cyclic stress response and cyclic stress strain curve shows that this alloy exhibits cyclic hardening.